Marine structural design - Bai, Yong; Jin, Wei-Liang (Butterworth-Heinemann is an imprint of Elsevier, 2016)
Describes the applications of structural engineering to marine structures. This work covers fatigue and fracture criteria that forms a basis for limit-state design and re-assessment of existing structures and assists with determining material and inspection requirements. It includes application of risk assessment to marine and offshore industries